2020
DOI: 10.3748/wjg.v26.i32.4729
|View full text |Cite
|
Sign up to set email alerts
|

New advances in radiomics of gastrointestinal stromal tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are uncommon neoplasms of the gastrointestinal tract with peculiar clinical, genetic, and imaging characteristics. Preoperative knowledge of risk stratification and mutational status is crucial to guide the appropriate patients’ treatment. Predicting the clinical behavior and biological aggressiveness of GISTs based on conventional computed tomography (CT) and magnetic resonance imaging (MRI) evaluation is challenging, unless the lesions have already metastasized at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 58 publications
(95 reference statements)
0
29
0
Order By: Relevance
“…Therefore, an objective and quantitative radiomics approach emerged. Radiomics has offered a novel approach to exploit information encompassed in medical images, which could extract numerous quantitative features from images and have exhibited to improve the preoperative prediction of high-malignant potential GISTs compared with the conventional imaging evaluation methods ( 7 , 16 , 19 , 34 ). Previous studies have demonstrated the predictive ability of radiomics features obtained from contrast-enhanced CT for the discrimination of risk rating of GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an objective and quantitative radiomics approach emerged. Radiomics has offered a novel approach to exploit information encompassed in medical images, which could extract numerous quantitative features from images and have exhibited to improve the preoperative prediction of high-malignant potential GISTs compared with the conventional imaging evaluation methods ( 7 , 16 , 19 , 34 ). Previous studies have demonstrated the predictive ability of radiomics features obtained from contrast-enhanced CT for the discrimination of risk rating of GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…The last application field that is worth mentioning is the gastrointestinal application. A plethora of studies on the new advances of radiomics applied to CT and MRI for the evaluation of gastrointestinal stromal tumors have been published, and the consequent potential clinical applications have been discussed [84]. Among these studies regarding the gastrointestinal stromal tumors, it is worth citing an interesting strategy developed for pattern classification based on the integration of radiomics and deep convolutional features [85].…”
Section: Radiomics In Clinical Practicementioning
confidence: 99%
“…Radiomics is defined as the process of extraction, analysis, and modeling of a large quantity of features from medical imaging dataset and to correlate this information to prediction parameters, such as clinical end-points, pathological and genomic features[ 65 ]. Radiomics is a complex process that can be divided into different phases, including: Acquisition of imaging dataset, tumor segmentation, feature extraction, exploratory analysis, and model building[ 66 ].…”
Section: Artificial Intelligence and Radiomic Ultrasound Analysismentioning
confidence: 99%